On standing one's ground - Sinclair, Neil (Oxford University Press, 2014)
I provide a positive expressivist account of the permissibility of ‘standing one’s ground’ in some cases of moral conflict, based in part on an illustrative analogy with political disputes. This account suffices to undermine Enoch’s recent argument against expressivism.